Botswana Development Policy Review : An Agenda for Competitiveness and Diversification - World Bank (World Bank, Washington, DC, 2017)
Botswana has been one of the most successful countries in the developing world over the last 40 years by many measures. Incomes have grown at a sustained pace, poverty has fallen, and the citizenry has become more educated. To be sure, poverty and income inequalities remain a problem, but rising standards of living have meant a better life for this generation of Batswana than any before it. The question facing the country leadership is whether this commendable performance can be sustained into the next generation. There are clouds on the horizon that cannot be ignored. Diamond earnings, the life blood of decades of prosperity, have flattened out. In per capita terms they are falling. Moreover, because revenues from diamonds going to the public sector have been falling for more than a decade, a growth model predicated upon an ever expanding state presence is not viable. Diamond earnings accruing to the state for subsequent redistribution have peaked. Employment and wages in the public sector have reached their natural limits as a share of Gross Domestic Product (GDP); recycling revenues from mining into the private sector, either directly or through the financial sector, has been inefficient with low social returns; and redistributive mechanisms to support social safety nets are also likely be approaching their limits. The country confronts the challenge of looking for new sources of growth outside of government.